To the problem of child studies in psychological and pedagogical heritage of A. Lazurskiy (early 20th century) - Inna Leoentyeva, Inna (Studia Europaea Gnesnensia, 2014)
Exploring the nature of a child, the child's personality, individual traits of character as well as peculiarities of formation and development in educational process is one of the main problems of modern pedagogy. The most significant contribution among scientists in the field of study of child and child’s individual features was made by A. Lazurskiy (1874-1917). The author determines that A. Lazurskiy was inclined to employ psychological knowledge in teaching practice and was deeply convinced that upbringing schoolchildren can rely on detailed and planned studies of child nature by means of psychological and pedagogical methods. Subsequently, the author demonstrates that A. Lazurskiy developed a versatile method for a holistic research of the personality of a child in the educational process – the natural experiment, and was the author of "experimental classes" as a valuable educational tools.